From darkness to light, from subject erasure to validation: personal writing by childhood victims of sexual abuse and sharing in therapeutic writing communities. - Sagi, Bella (Journal of Poetry Therapy, 2026)
The article reviews the current theoretical research on writing in the aftermath of childhood sexual trauma and the role of writing and of sharing in therapeutic online writing communities. This paper presents a qualitative narrative study that included analysis of 54 texts written and shared on the internet. The paper suggests that personal writing by childhood victims of sexual abuse and online sharing of their texts facilitate testimony and rehabilitation of the abused and erased self. In the discussion of the research findings, I focus on the role of writing in revealing the truth, and the possibility of existing in a dialectics of trauma. The paper demonstrates this through the salient theme of silence and speech. The theoretical contribution of the study to the fields of bibliotherapy and poetry therapy is in understanding the role and meanings of writing and of sharing in therapeutic writing communities.